2022
DOI: 10.3390/membranes12050488
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of Latex Particles to Evaluate Critical Process Parameters in Steric Exclusion Chromatography

Abstract: The steric exclusion chromatography (SXC) is a rather new method for the purification of large biomolecules and biological nanoparticles based on the principles of precipitation. The mutual steric exclusion of a nonionic organic polymer, i.e., polyethylene glycol (PEG), induces target precipitation and leads to their retention on the chromatographic stationary phase. In this work, we investigated the application of latex particles in the SXC by altering the particle’s surface charge as well as the PEG concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This indicated trends for the maximum loading volume in SXC for increased PEG concentrations and for reduced pH values. Similar findings were reported before for Orf virus (Eilts, Lothert, Orbay et al, 2022) and for latex particles (Eilts, Steger, Lothert & Wolff, 2022b). However, the final precipitate sizes were expected to vary between the static experiments and the dynamic SXC runs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicated trends for the maximum loading volume in SXC for increased PEG concentrations and for reduced pH values. Similar findings were reported before for Orf virus (Eilts, Lothert, Orbay et al, 2022) and for latex particles (Eilts, Steger, Lothert & Wolff, 2022b). However, the final precipitate sizes were expected to vary between the static experiments and the dynamic SXC runs.…”
Section: Discussionsupporting
confidence: 90%
“…This was expected as PEG is the driving force of SXC, causing the association of the viral particles and their accretion to the stationary phase (Lee et al, 2012), and was predicted by the offline precipitation kinetics for the KHV cell culture supernatant (Figure 6). Nevertheless, the PEG concentration was shown to be a limiting factor in SXC applications, due to two reasons: on one hand, high viscosities of the PEG solution hinder high flow rates and cause high backpressure (Eilts, Lothert, Orbay et al, 2022); on the contrary, by the formation of large precipitates, filtration effects on the membrane stationary phase induce pore blockages (Eilts, Steger, Lothert, & Wolff, 2022b; Lothert, Sprick, Beyer et al, 2020; Figure 1c). In this study, an interesting effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the stationary phases for SXC, it can be observed that cellulose membranes were predominantly used, either in a stabilized or non-stabilized form. The membranes from Cytiva and Sartorius were punched and either assembled manually into appropriate stainless-steel housings [18,[22][23][24][25][26][27][28][29] or overmolded with an injection molding machine [16]. Ready-to-use membrane modules for SXC are commercially available from ContiVir offering CaptuVir™ modules [30].…”
Section: Stationary Phasesmentioning
confidence: 99%
“…SXC studies relying on membranes as a stationary phase used stacked membrane layers assembled in their housing (e.g., a stainless-steel holder for multi-use or an overmolded plastic housing for single-use) so that the flow was directed frontally from above, resulting in a dead-end flow [ 19 ]. Membrane devices of a diameter between 13 mm and 25 mm with 10 to 20 layers of stacked membranes have been employed in previous publications on SXC [ 11 , 12 , 14 , 15 , 20 , 21 , 22 , 23 ]. However, a deep mechanistic understanding of the requirements of the membrane device is lacking, especially concerning the potential scaling up of SXC.…”
Section: Introductionmentioning
confidence: 99%